The Influence of Sinetron Shows From the Middle School Window on SMPN 1 Naringgul Student Behavior - Mesi Nuraeni; M. Izul Fikri Pratama (Journal Basic Science and Technology, 2021)
This study focuses on the views of SMPN 1 Naringgul students on the soap opera Dari Jendela SMP. The purpose of this study was to determine the perception, behavior, and influence of the soap opera Dari Jendela SMP. The method used in this research is a qualitative research method. Methods of data collection is done through interviews and direct observation. The source of the data taken is primary data which is data obtained directly from students through the interview and observation process. The data analysis techniques used are data reduction, data presentation and conclusion drawing. Participants are students of SMPN 1 Naringgul. The results showed that they liked the soap operas, even the soap operas could change their thinking patterns and tended to follow the behavior of the Dari Jendela SMP.